Effect of Turbulence Intensity on Low Reynolds Number Airfoil Aerodynamics - Kumar Gupta, Ashish; A. Aswatha Naray, P.; Ramesh, G. (International Journal of Engineering and Technology, 2018)
The flow transition over the airfoil at low Reynolds number influences its aerodynamic performance; hence this is being studied by many researchers in the recent times. One of the important factors affecting flow transition is the turbulence intensity of the oncoming flow that has not been well addressed. Here a systematic study on a few of Low Reynolds number airfoils is made though viscous- inviscid interaction code XFLR to understand the sensitivity of the inlet turbulence on the flow transition. The analyses with XFLR5 code were made at three Reynolds number and three different turbulent intensity values. The analysis brings out clearly the sensitivity of the flow to turbulent intensity. The reason for the drag increase and scatter in the experimental data has been investigated which is seen in case of E387 airfoil for Reynolds number below 100,000.Â Â